(untitled) (Proceedings of the International Conference on Public Health, 2017)
Acute respiratory infections (ARIs) are the leading cause of morbidity and mortality from infectious disease worldwide, particularly affecting the youngest and oldest people in low and middle-income nations (WHO, 2014). There were some areas in East Java with ARIs among under five years children is high enough, one of Surabaya with 4,306 cases (Surabaya Health District, 2015). The aim of this research was to describe best practices to decrease acute respiratory infections in under five years children in the primary health care. This research was an observational study with cross sectional design. Research sample was 5 primary health care with highest cases from 2014 to 2015. Data collection were carried out with questionnaire, observation form and analyzed using descriptive method. The result showed that all primary health care have guidance for infection prevention and control measures but not well implemented. There were 3 primary health care have support unit and staff to solve the infection diseases named sanitation clinic unit that responsible for identify diseases, communicate with community, observation housing sanitation, give recomendation to the community, and also do the surveillance for environment based diseases. These guidelines and sanitation clinic unit will contribute to improving health care practices in Indonesia